An Exploration of Young People’s Perceptions of what Contributes to Positive Wellbeing within Education - Riley, Hollie (2021)
An increasing focus is being placed on the wellbeing and mental health of children and young people (CYP) in education, through government policy, initiatives and guidance (Department of Health (DoH) & Department for Education (DfE), 2017; DfE and DoH, 2015; Children and Families Act, 2014), with the UK Government regularly measuring indices of CYP’s wellbeing (Office for National Statistics, 2018). Despite an increasing focus being placed on wellbeing and its importance, many CYP continue to report not being happy with their lives (DfE, 2019a).